Analisis Faktor Resiko Kejadian Pneumonia Pada Balita di Wilayah Kerja Puskesmas Sidorejo Kota Pagar Alam - Indah, Nusa; Suryani, Lilis; Rosalina, Santi (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2022)
Pneumonia is an infectious disease that is still a health problem in Indonesia, the third leading cause of death in Indonesia after cardiovascular and tuberculosis. The high incidence of pneumonia mainly attacks the age group of infants and toddlers. The purpose of this study was to determine the analysis of risk factors for pneumonia in children under five in the working area of ??the Sidorejo Health Center, Pagar Alam City in 2021, this study was a retrospective study with a case control approach. The research subjects consisted of two groups, namely the case group and the control group, each of which consisted of 63 subjects. Data was collected by means of interviews, observations and measurements. Data analysis used univariate, bivariate with chi square and multivariate analysis to determine the most dominant influence of the independent variables on the dependent variable. The analysis was carried out on the variables related to the bivariate analysis with a p value < 0.25 and an interval value of 95% CI not below 1. The analysis was carried out using logistic regression test with forward stepwise (conditional) with = 0.05 as a reference in decision making. test results. The results of this study that of the 12 variables studied, there are 6 variables that are at risk for the incidence of pneumonia in toddlers, namely ventilation, lighting, temperature, humidity, smoking habits, history of breastfeeding, the variable most at risk for the incidence of pneumonia in toddlers is lighting. In this study, it can be concluded that the floor of the house, the proportion of ventilation, the intensity of natural lighting (sunlight), temperature, humidity; occupancy density, smoking habit in the house, history of family members suffering from respiratory tract infections, type of fuel for cooking, nutritional status, immunization status and history of breastfeeding, have a relationship with the incidence of pneumonia.